Doses de Flobond® no crescimento inicial de mudas pré-brotadas de cana-de-açúcar sob estresse hídrico - Bezerra, João Vitor da Silva (Universidade Federal de São Carlos, 2025)
Sugarcane (Saccharum officinarum) is one of the most prominent crops in Brazil, playing a key role in agribusiness, especially in the production of bioenergy, ethanol, and sugar. However, the sugarcane production sector faces issues such as declining yields and reduced longevity of plantations, which has increased the search for techniques to improve crop productivity. In this context, one technology that may help address this bottleneck is the use of sugarcane MPBs (Pre-Sprouted Seedlings), which ensure quality, health, and traceability at a lower short-term cost. Nevertheless, in order to raise productivity levels, the application of plant stimulants is necessary, aiming at quantitative increases in production, growth under water stress, and longer survival periods. Thus, four treatments were designated: Treatment 1 received no dose of the product and served as a “control”; Treatment 2 received a dose equivalent to 2L of the product per hectare; Treatment 3: 4L; and Treatment 4: 8L, respectively, after the MPB planting in a greenhouse. The following parameters were evaluated: stalk diameter, plant height growth over time, number of tillers, and plant survival after planting. The experimental design was completely randomized with 12 replications, totaling 48 plots. The averages obtained were subjected to Tukey's test (5%). Treatments 1, 2, 3, and 4 showed no significant differences in the initial growth of seedlings under the experimental conditions; however, Treatment 4 showed significant differences in seedling survival, followed by Treatments 3 and 2.
Flobond® doses on the initial growth of pre-sprouted sugarcane seedlings under water stress
Keywords: Estimulante; MPBs; Estresse hídrico; Stimulant; Water Stress; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA